Core–shell structured Li0.33La0.56TiO3 perovskite as a highly efficient and sulfur-tolerant anode for solid-oxide fuel cells1. Issue 16 (28th April 2015) - Wang, Wei; Qu, Jifa; Zhao, Bote; Yang, Guangming; Shao, Zongping
<x xml:space="preserve">Abstract</x> Core–shell structured Li0.33La0.56TiO3 perovskite is proved to be an active and sulfur-tolerant anode for solid oxide fuel cells.